Analysing sectoral competitiveness: A framework of strategic management - D'Artis Kancs; Julda Kielyte (Journal for East European Management Studies, 2001)
In recent years, some major industries in transition economies, such as food and beverage, once epitomised industrial supremacy have lost significant market shares to it.s foreign competitors, both at home and abroad. Recognising the fact once pre-eminent world-wide economic position of former socialist economies has generally eroded significantly in recent years. Our study examines the competitive implications of the major determinants of competitiveness within a framework favoured by the Strategic Management theory in selected transition economies. Our research focuses on the three Baltic States and two of their major competitors within the Europe -Germany and EU in general. The main objective of our study is, therefore, to develop an analytical framework for analysing industrial competitiveness and to apply it to the food sector and it's related industries in these economies. – – Seit einigen Jahren haben große Industriebereiche wie Lebensmittel- und Getränkeindustrie, einst überlegene Industriezweige, große Marktanteile an fremde Konkurrenzunternehmen abgeben müssen, sowohl im eigenen Land als auch im Ausland. In unserer Arbeit untersuchen wir die Auswirkungen der Hauptfaktoren des Wettbewerbs im Rahmen der Theorie des Strategic Management in ausgewählten im Wandel begriffenen Volkswirtschaften. Unser Hauptaugenmerk liegt auf drei baltischen Staaten und deren Hauptkonkurrenten . Deutschland und die EU im ganzen. Unser Hauptziel stellt dabei die Entwicklung eines Rahmens dar, mit dessen Hilfe industrieller Wettbewerb analysiert werden kann. Dieser Rahmen wird auf die Lebensmittelindustrie und verwandte Zweige in den entsprechenden Staaten angewendet.
Keywords: 650